Social Media and Attitude Change: Information Booming Promote or Resist Persuasion? - Wang, Yizhi; Dai, Yuwan; Li, Hao; Song, Lili (Frontiers in Psychology, 2021)
Emerging social media platforms such as Twitter and its Chinese equivalent Weibo have become important information sharing and communication platforms. In addition, they also gradually show stronger guidance to public opinion. Comparing to traditional media, these platforms have salient characteristics such as high information dissemination efficiency and interactive commentary which would contribute to high information overload. How does this affect users’ attitude change? To answer this question, this study aimed to measure participants’ attitudes change after reading Weibo posts related to street vendors. A 2 (Post attitude: positive posts vs. Negative posts) × 4 (Reading time: 35min vs. 25min vs. 15min vs. 5min) experiment was set up and SC-IAT(Single Category Implicit Attitudes Test) was used to measure the implicit attitudes. The interaction effect revealed that less reading time which meant high information overload condition had a stronger influence in both positive and negative posts. Users are more easily to be persuaded by posts under high overload. Furthermore, the users’ attitude change was not simply stronger with more information. There were obedience firstly, resistance, and acceptance three stages and different mechanisms.